Memaksimalkan Kinerja dengan Mengelola Job Description dan Beban Kerja (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Improving performance is certainly not easy because companies must pay attention to many things such as job descriptions and workload. The goal to be achieved in this study is to maximize performance by managing job descriptions and workload. This study involved 36 people and involved all members of the population as respondents using the census method. The data is tested by performing multiple linear regression. The results of the deterministic analysis show that job descriptions and workload affect employee performance by 78.4 percent. Job descriptions partially affect performance positively and significantly, while workload partially affects performance negatively and significantly. Simultaneous testing shows the results that job description and workload significantly affect performance. Research advice is to maximize job descriptions and reduce workload.